"Release and Catch" Effect of Perfluoroalkylsulfonylimide‐Functionalized Imidazole/Pyridine on Brønsted Acids in Organic Systems. Issue 21 (23rd September 2016) - You, Li; Ren, Xiao‐Fei; Wang, Yun; Ma, Zhong‐Hua; Gu, Yanlong; Ma, Jing‐Zhong
Abstract: A "release and catch" method was developed by utilising the scavenging effect of a fluorous zwitterion on a homogeneous triflic acid (TfOH) catalyst in Michael addition and Rupe rearrangement. Both TfOH and the zwitterion were recycled with >90 % recovery using toluene. The zwitterions were designed by functionalising imidazole/pyridine with the perfluoroalkylsulfonylimide group. The "caught" TfOH was delivered to ethyl acetate and re‐used. The smooth delivery was primarily because of the fluorous tail of the zwitterion, the hydrophobicity of which probably weakened the ability of the zwitterion to form H bonds, so that retro‐ion‐exchange occurred towards the formation of the acid and zwitterion. The method was universal for other strong Brønsted acids such as H2 SO4 and p ‐MeC6 H4 SO3 H. The method combined the significant advantages of homogeneous catalysis and heterogeneous isolation. Based on the H 0 acidity function and the 31 P NMR chemical shift of Et3 P=O adducts, it is reasonable to deduce that the decrease of the acid strength of the formed composites of Brønsted acids and the zwitterion drove the scavenging effect. Abstract : Catch me if you can : A "release and catch" method is developed by utilizing the scavenging effect of a fluorous zwitterion on a homogeneous triflic acid (TfOH) catalyst in Michael addition and Rupe rearrangement. Both TfOH and the zwitterion were recycled with >90 % recovery using toluene. The zwitterions were designed by functionalizing imidazole/pyridine with the perfluoroalkylsulfonylimide group.